Self-Assembled Monolayers of n-Dodecanethiol on Nickel Surfaces Using 2-Hydroxyethylammonium Formate as Reducing Medium. Issue 4 (1st January 2017) - Rajalingam, S.; Devillers, S.; Dilimon, V. S.; Delhalle, J.; Mekhalif, Z.
Abstract : The formation of stable self-assembled monolayers of organothiol molecules on nickel (Ni) surfaces is hindered by the presence of oxides layers. In this work, 2-hydroxyethylammonium formate ionic liquid (HEAF) is shown to be an efficient medium for the electrochemical reduction of the Ni oxide layer present on the surface of polycrystalline Ni substrates. The so formed oxide free Ni surface is found to be very suitable for the preparation of self-assembled monolayers of n -dodecanethiol ( n -C12 SH). X-ray photoelectron spectroscopy, polarization modulation infrared reflection absorption spectroscopy, water contact angle measurements and electrochemical techniques are used for the characterization of the monolayers. The results show the formation of self-assembled monolayer with good molecular orientation and surface coverage. Electrochemical impedance measurements (EIS) indicate a surface coverage up to 99% after 18 h of self-assembly in n -C12 SH containing ethanol solutions.